Experimental, numerical simulation and mathematical modelling of vane type vertical axis wind turbine - Kadhim Hussein Suffer, Al-Zaedy (Universiti Malaysia Perlis (UniMAP), 2016)
Doctor of Philosophy in Mechanical Engineering